2020
DOI: 10.1007/s00401-020-02131-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation age acceleration is associated with ALS age of onset and survival

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 10 publications
2
39
2
Order By: Relevance
“…Third, we do not replicate the recently reported association between epigenetic age acceleration and survival 81 . Importantly, in our analyses we adjusted for sampling age, as it has been shown to be crucial when studying epigenetic age acceleration 82 , especially given that age of onset affects disease progression in ALS 83 .…”
Section: Discussioncontrasting
confidence: 99%
“…Third, we do not replicate the recently reported association between epigenetic age acceleration and survival 81 . Importantly, in our analyses we adjusted for sampling age, as it has been shown to be crucial when studying epigenetic age acceleration 82 , especially given that age of onset affects disease progression in ALS 83 .…”
Section: Discussioncontrasting
confidence: 99%
“…18 A study of genetically unexplained ALS patients (n = 249) also revealed a strong reverse correlation of DNAmage acceleration with disease onset and survival. 19 A 5-year increase in DNAm-age acceleration was linked to a 6.4-year earlier onset using blood collected at ALS diagnosis and 8.5year earlier onset using CNS tissues, indicating further acceleration of DNAm-age by the end-stage of disease.…”
Section: Studies Of Dnam Clocks In Neurodegenerative Diseasesmentioning
confidence: 86%
“…DNAm-age acceleration (difference between DNAm-age and chronological age) was associated with major neurodegenerative diseases, such as AD, 15 Parkinson disease (PD), 16 Huntington disease 17 and amyotrophic lateral sclerosis (ALS). 18,19 Similarly, HIV-infected individuals exhibit premature aging based on methylome-wide changes and Horvath DNAm clock. 20,21 Furthermore, individuals with Werner or Down syndromes also display accelerated DNAm clocks.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, we additionally demonstrated that a risk score based on DNA methylation of three identified sites predicts disease duration. Work from Zhang et al recently demonstrated that DNA methylation age acceleration associated with ALS survival [ 65 ]. The finding that DNA methylation levels on two sites ( KIAA0513 and UHRF1 ) refined survival information driven by PRNP codon 129 genotype is informative, particularly for individuals most at risk.…”
Section: Discussionmentioning
confidence: 99%